Cannabis induced psychosis - an overview - Chandran, Rabindran; Verma, Mamta (International Journal of Medical Research and Review, 2017)
Psychosis is a condition where there is a loss of contact with reality with symptoms like delusions, hallucinations, paranoia, disorganized thinking & speech, loss of motivation, depression, anxiety & poor sleep. It can be associated with Schizophreniform disorder, Bipolar disorder, Schizoaffective disorder, Depression with psychotic features, Drug-induced psychosis, Organic psychosis or Post-traumatic stress disorder. Psychosis is so common that about 3 out of every 100 people will have a psychotic episode in their lifetime. The phases of psychosis include an initial Prodromal Phase where there is subtle changes in thinking, perception and behavior. During acute Phase full blown symptoms occur which may affect the individual’s daily living. Later Recovery Phase starts.